2007
DOI: 10.1242/dev.02712
|View full text |Cite
|
Sign up to set email alerts
|

Tbx4is not required for hindlimb identity or post-bud hindlimb outgrowth

Abstract: Tbx4 is a crucial gene in the initiation of hindlimb development and has been reported as a determinant of hindlimb identity and a presumptive direct regulator of Fgf10 in the limb. Using a conditional allele of Tbx4, we have ablated Tbx4 function before and after limb initiation. Ablation of Tbx4 before expression in the hindlimb field confirms its requirement for limb bud outgrowth. However, ablation of Tbx4 shortly after onset of expression in the hindlimb field, during limb bud formation, alters neither li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 46 publications
9
91
0
Order By: Relevance
“…Both studies reach identical conclusions: Tbx4 and Tbx5 are required during the initial phase of limb initiation but are dispensable for continued limb outgrowth (Hasson et al, 2007;Naiche and Papaioannou, 2007) (Fig. 2B).…”
Section: Tbx4 and Tbx5 Have Temporally Distinct Roles During Limb Devsupporting
confidence: 55%
“…Both studies reach identical conclusions: Tbx4 and Tbx5 are required during the initial phase of limb initiation but are dispensable for continued limb outgrowth (Hasson et al, 2007;Naiche and Papaioannou, 2007) (Fig. 2B).…”
Section: Tbx4 and Tbx5 Have Temporally Distinct Roles During Limb Devsupporting
confidence: 55%
“…In mice, however, it has been suggested that these two T-box genes initiate limb bud development by inducing Fgf10 in the mesenchyme, but are not involved in establishing limb identity (Naiche and Papaioannou, 2003;Minguillon et al, 2005;Naiche and Papaioannou, 2007). The molecular mechanisms of forelimb and hindlimb specification are not completely understood.…”
Section: Resultsmentioning
confidence: 99%
“…22 TBX4 is a known transcriptional target of PITX1 26,27 and is required for normal hindlimb development, [28][29][30][31] further supporting a role for the PITX1-TBX4 developmental pathway in talipes equinovarus etiology. Furthermore, PITX1 and TBX4 are two genes that are specifically expressed in the hindlimb compared with the forelimb, providing an explanation for the selective limb phenotype.…”
Section: Introductionmentioning
confidence: 88%
“…10 Interestingly, several genes located within the talipes equinovarus CNVs are specifically expressed in the hindlimb compared with the forelimb or known to be involved in early embryonic patterning. PITX1 and TBX4 are transcription factors that are essential for normal lower limb development 17,28,29,51 and CNVs involving each are associated with talipes equinovarus. 18,22,52 Although we identified recurrent duplications of chromosome 17q23 involving TBX4 in this report, reciprocal deletions have also been associated with talipes equinovarus.…”
Section: Copy Number Analysis In Talipes Equinovarusmentioning
confidence: 99%